Highly Reliable Sensitive Capacitive Tactile Sensor with Spontaneous Micron‐Pyramid Structures for Electronic Skins. Issue 10 (2nd August 2022) - Zhao, Le; Yu, Shihui; Li, Junjun; Song, Zichen; Wang, Xiuyu
Abstract: In recent years, it is still challenging to develop a capacitive tactile sensor with low cost, high sensitivity, and controllable morphology. Herein, the flexible capacitive pressure sensor (FCPS) with high sensitivity is fabricated via a one‐step template method to produce spontaneous micron‐pyramid structured polydimethylsiloxane (PDMS) by releasing a four‐way stretched PDMS film treated with ultraviolet ozone exposure. The capacitive sensor is composed of two silver nanowire electrodes coated on polyimide substrate and a patterned PDMS dielectric layer sandwiching in the middle, exhibits an ultrahigh sensitivity of 15.66 kPa −1, an ultralow limit of detection of 0.2 Pa, a fast response time of 42.4 ms, and excellent cycling stability. The finite‐elemental analysis suggests that the uniform micro‐pyramid structures are vital to obtain ultrahigh sensitivity, low detection limit, and fast response. In particular, the FCPS can keep the tactile performance unchanged after 4000 repeated tests, reflecting the high robustness. In conclusion, the significant advantages of the sensor enable it to be well applied in the fields of sign language detection, spatial pressure distribution, and physiological signal monitoring, indicating that FCPS has a potential application prospect in the fields of flexible wearable electronic devices and electronic skins. Abstract : This paper reports an efficient strategy to fabricate highly sensitive flexible capacitive pressure sensor based on a pyramid polydimethylsiloxane (PDMS) microstructure via a feasible low‐cost fabrication approach.The pressure sensor obtained in this work can provide high sensitivity (15.66 kPa −1 ), ultra‐low detection limit (0.2 Pa), fast response time (42.4 ms), and excellent stability in repeated loading and bending tests (4000 times).